The anti-aging gene KLOTHO is a novel target for epigenetic silencing in human cervical carcinoma - Jaehyouk Lee; Dongjun Jeong; Jin‐Sun Kim; Soonduck Lee; Jin-Hwa Park; Boogi Chang; Samil Jung; Lisha Yi; Young‐Soo Han; Young Yang; Keun Tae Kim; Jong‐Seok Lim; et al. (2010)
Klotho was originally characterized as an anti-aging gene that predisposed Klotho-deficient mice to a premature aging-like syndrome. Recently, KLOTHO was reported to function as a secreted Wnt antagonist and as a tumor suppressor. Epigenetic gene silencing of secreted Wnt antagonists is considered a common event in a wide range of human malignancies. Abnormal activation of the canonical Wnt pathway due to epigenetic deregulation of Wnt antagonists is thought to play a crucial role in cervical tumorigenesis. In this study, we examined epigenetic silencing of KLOTHO in human cervical carcinoma.Loss of KLOTHO mRNA was observed in several cervical cancer cell lines and in invasive carcinoma samples, but not during the early, preinvasive phase of primary cervical tumorigenesis. KLOTHO mRNA was restored after treatment with either the DNA demethylating agent 2'-deoxy-5-azacytidine or histone deacetylase inhibitor trichostatin A. Methylation-specific PCR and bisulfite genomic sequencing analysis of the promoter region of KLOTHO revealed CpG hypermethylation in non-KLOTHO-expressing cervical cancer cell lines and in 41% (9/22) of invasive carcinoma cases. Histone deacetylation was also found to be the major epigenetic silencing mechanism for KLOTHO in the SiHa cell line. Ectopic expression of the secreted form of KLOTHO restored anti-Wnt signaling and anti-clonogenic activity in the CaSki cell line including decreased active beta-catenin levels, suppression of T-cell factor/beta-catenin target genes, such as c-MYC and CCND1, and inhibition of colony growth.Epigenetic silencing of KLOTHO may occur during the late phase of cervical tumorigenesis, and consequent functional loss of KLOTHO as the secreted Wnt antagonist may contribute to aberrant activation of the canonical Wnt pathway in cervical carcinoma.